1990
DOI: 10.1039/ft9908602035
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton ionization processes in HCl studied by photoelectron spectroscopy

Abstract: A (2 + 1) REMPI-PES study of HCI has been carried out in t h e two-photon energy region between 77000 a n d 85500 cm-'. The observed 'A(2), 'A(2), 'II(l) and 'X-(O+) states are characterized as Rydberg states. The one-photon ionization of t h e B 'X+ state has been shown to be dominated by indirect processes involving competition between electronic autoionization and dissociation via superexcited states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…For HCl a second avoided crossing of the V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ produces a new set of adiabatic curves, 27 of which the lower one, the B 1 ͚͑0 + ͒ state, has two minima and an electronic configuration that changes with the internuclear distance. [6][7][8][9]23 For HBr a similar double minimum state is formed by an avoided crossing of the respective V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ state. [6][7][8][9]23 For HBr a similar double minimum state is formed by an avoided crossing of the respective V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ state.…”
Section: Introductionmentioning
confidence: 99%
“…For HCl a second avoided crossing of the V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ produces a new set of adiabatic curves, 27 of which the lower one, the B 1 ͚͑0 + ͒ state, has two minima and an electronic configuration that changes with the internuclear distance. [6][7][8][9]23 For HBr a similar double minimum state is formed by an avoided crossing of the respective V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ state. [6][7][8][9]23 For HBr a similar double minimum state is formed by an avoided crossing of the respective V 1 ͚͑0 + ͒ state with the E 1 ͚͑0 + ͒ state.…”
Section: Introductionmentioning
confidence: 99%
“…1, which is a composite of available data, calculations, and comparison to HCl. 8,16,17 In this paper, we present a study of the dynamics of Rydberg E( 1 ⌺ ϩ ) state/ion-pair state V( 1 ⌺ ϩ ) using a femtosecond laser pump-probe technique coupled with reflectron time-of-flight mass spectrometry. The lifetime of HBr in this state is determined over a range of pump laser wavelengths and the influence of deuterium isotope substitution is also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…5,[12][13][14][15] Spectra and images of those states were therefore only used to aid laser wavelength calibration and to assign the fragmentation channels in the images. The spectroscopy and ionization dynamics of the g and F state confirmed previous reports and contained no surprises.…”
Section: Resultsmentioning
confidence: 99%
“…In a photoelectron spectroscopic experiment, de Lange and co-workers have shown that the main source of photoelectrons arising from excita-tion of the ϭ9 level of the V 1 ⌺ ϩ (0 ϩ ) state is the photoionization of the excited hydrogen and chlorine atoms formed following dissociation of a superexcited state. 5 Based on earlier work by Lefebvre-Brion and Keller, 6 it was suggested that this state is a 1 ⌺ ϩ (0 ϩ ) state derived from a (5 1 2 4 )4s configuration, i.e., the lowest member of a Rydberg series converging to the first excited state of the HCl ϩ ion. 2 There exists therefore plenty of evidence that the direct ionization of those Rydberg states which may mix with the ion pair state will have to compete with photodissociation into excited state atoms, through a superexcited ''gateway'' state.…”
Section: Introductionmentioning
confidence: 99%